"Differentiated Instruction in Teaching Communication and Research in Filipino Language and Culture and It’s Effect to the Senior High School Students’ Learning - RIVERA, MARIE GRACE; MANGINDRA, ANESA (International Journal of Arts, Sciences and Education, 2025)
This study investigates the effectiveness of Differentiated Instruction (DI) in teaching Communication and Research in Filipino Language and Culture to Senior High School students during the 2021-2022 school year. The research utilized a quasi-experimental design, involving two distinct groups of students: the control group, which followed the traditional online lecture-discussion approach, and the experimental group, which was taught using online differentiated instruction. To assess the students’ learning progress, both groups completed pretests and posttests. The results revealed that both groups scored low on the pretest, indicating a similar starting point in their understanding of the subject matter. However, upon administering the posttest, both groups showed improvement, but the experimental group significantly demonstrated a better performance than controlled group.. This suggests that the online differentiated instruction strategy had a more substantial positive impact on student learning compared to the traditional method. Further analysis of the mean gain scores between the two groups revealed that the experimental group demonstrated larger improvement than the control group. This highlights the effectiveness of differentiated instruction, particularly when applied online, in enhancing students' academic performance in Filipino Language and Culture. While both groups showed progress after the instructional sessions, the experimental group, which was exposed to the modern, student-centered approach of differentiated instruction, exhibited greater gains compared to the traditional lecture-based approach. In conclusion, the findings from the pretest and posttest results, along with the mean gain scores, suggest that differentiated instruction is a highly effective teaching strategy for improving student learning in Communication and Research in Filipino Language and Culture. The study highlights the importance of employing differentiated instructional methods, particularly in the context of online learning during the "new normal," where diverse learning needs must be addressed. By tailoring instruction to meet the varying needs of students, whether online or through other modalities, differentiated instruction significantly enhances the learning experience and outcomes, offering a more effective way to support students' academic growth and success in an evolving educational landscape.